Seizing the Opportunity: Dynamics of the Salafi-Wahabi Movement in Turkey - Sujibto, B.J.; Filiz, Ikram (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2023)
Being a secular state after centuries under the Islamic sultanate of the Ottoman Empire, Turkey has been challenged by various internal political turmoil and controversies over religion and its relation to the state. As such, fierce debate has become unavoidable for Islamist and revivalist groups that feel discriminated against for practicing Islam in public spaces. This article discusses Salafism and Wahabism in contemporary Turkey, starting from its inception to its da'wah and development strategies in society. The article used a qualitative approach with a literature review. The data was collected from secondary sources, including research results by scholars and various pieces of information in the mass media that emerged during the era of Recep Tayyip Erdogan until 2022. This article scrutinizes (1) the history of the resurgence of Salafism and Wahabism in Turkey due to the influence of the social and political situation; (2) pro-Islamic political policies in the government providing an opportunity for Salafi and Wahabi to develop in Turkey; and (3) the form and strategy of a pro-active and non-confrontational Salafi group in Turkey. This third part is very urgent for this article because it relates to secular Turkey's social, political, and cultural contexts.